Green Flags and headache: A concept study using the Delphi method. Issue 2 (6th January 2021) - Pohl, Heiko; Do, Thien Phu; García‐Azorín, David; Hansen, Jakob Møller; Kristoffersen, Espen Saxhaug; Nelson, Sarah E.; Obermann, Mark; Sandor, Peter S.; Schankin, Christoph J.; Schytz, Henrik Winther; Sinclair, Alexandra; Schoonman, Guus G.; et al.
Abstract: Objective: The aim of this study was to collect and rate Green Flags, that is, symptoms or pieces of information indicating that a patient is more likely to suffer from a primary than from a secondary headache. Background: When assessing headaches, a central question to be answered is whether the pain is primary or secondary to another disorder. To maximize the likelihood of a correct diagnosis, relevant signs and symptoms must be sought, identified, and weighed against each other. Methods: The project was designed as a Delphi study. In the first round, an expert panel proposed green flags that were rated anonymously in two subsequent rounds. Proposals with an average rating of 4.0 and higher on a scale from 0 to 5 reached consensus. Results: Five Green Flags reached consensus: (i) "The current headache has already been present during childhood"; (ii) "The headache occurs in temporal relationship with the menstrual cycle"; (iii) "The patient has headache‐free days"; (iv) "Close family members have the same headache phenotype"; and (v) "Headache occurred or stopped more than one week ago." Conclusions: We propose five Green Flags for primary headache disorders. None being a pathognomonic sign, we recommend searching for both Green Flags and Red Flags. If both are present, a secondary headache should be suspected. Overall, the application of the Green Flag concept in clinical practice is likely to increase diagnostic accuracy and improve diagnostic resource allocation. Prospective studies in clinical populations should be conducted to validate these Green Flags.